Tricuspid regurgitation: frequency, management and outcome among patients with severe left-sided valvular heart disease in Europe. Insights from the ESC-EORP valvular heart disease II survey. (3rd October 2022) - Dreyfus, J; Komar, M; Attias, D; De Bonnis, M; Ruschitzka, F; Popescu, B A; Laroche, C; Tribouilloy, C; Prokophiev, A B; Mizariene, V; Bax, J J; Maggioni, A P; et al.
Abstract: Background: Tricuspid regurgitation (TR) is frequent among patients with severe left-sided valvular heart disease (LS-VHD). Objectives: This study sought to assess TR frequency, management and outcome in this population. Methods: Among 6883 patients with severe LS-VHD or previous valvular intervention in the EURObservational Research Programme prospective VHD II survey, we analyzed frequency and grade of TR according to LS-VHD, and 6-month survival according to TR grade. Among 2081 patients who underwent an intervention for severe LS-VHD, we analyzed frequency and outcome of concomitant TV intervention, and concordance between Class I indications for concomitant TV surgery (patients with severe TR) and real-practice decision-making. Results: Moderate to severe TR was very frequent among patients with severe mitral VHD (≥30%), especially in patients with secondary mitral regurgitation (46%), and rare among patients with aortic VHD (<5%). Higher TR grade was associated with a poorer 6-month survival (P<0.001). Rates of concomitant tricuspid valve (TV) intervention at the time of left-sided heart valve surgery were high at the time of mitral valve surgery (more than 40%). Concomitant TV intervention at the time of left-sided heart valve surgery (LS-HVS) was not associated with an increase in-hospital mortality (P=0.93). Concordance between Class I indications for concomitant TV surgery at the time of LS-HVS according to guidelines and real-practice decision-making was very good (88% overall). Conclusion: TR was frequent in patients with mitral VHD and was associated with a poorer outcome as TR grade increased. Compliance to guidelines for Class I indications for concomitant TV surgery at the time of LS-HVS was very good. With the trend toward more transcatheter treatment for left-sided VHD, there is a critical need for safe and efficient tricuspid valve transcatheter treatment for patients with concomitant TR. Funding Acknowledgement: Type of funding sources: None.